A case of familial adenomatous polyposis with protein‐losing enteropathy treated by laparoscopic total colorectal resection: A literature review. Issue 1 (2nd July 2022) - Tubakihara, Hiroki; Sawayama, Hiroshi; Komohara, Yoshihiro; Miyamoto, Yuji; Ogawa, Katsuhiro; Ohuchi, Mayuko; Yoshida, Naoya; Baba, Hideo
Abstract: Familial adenomatous polyposis (FAP) with protein‐losing enteropathy is a rare disorder and is difficult to treat medically. A 74‐year‐old female patient was referred to our hospital with a chief complaint of anorexia. Lower gastrointestinal endoscopy showed multiple adenomas from the ascending colon to the rectum and adenocarcinoma in the sigmoid colon and descending colon. Laboratory findings showed hypoalbuminemia (albumin 1.6 mg/dl). Protein leak scintigraphy using 99mTc‐HSAD found a protein leak from the colon. Although hypercaloric infusion was administered, the nutritional status was not improved and albumin transfusion was required. The patient underwent laparoscopic total proctocolectomy, ileal pouch‐anal anastomosis, and temporary ileostomy. She had a good postoperative course and the hypoalbuminemia normalized in a few weeks. The patient underwent temporary ileostomy reversal. Here we report a case of FAP with protein‐losing enteropathy who underwent laparoscopic total proctocolectomy, which resulted in improvement of the protein leak as well as cancer treatment.